Variceal bleeding in cirrhotic patients: What is the best prognostic score? - Asmaa N. Mohammad; Khairy H. Morsy; Moustafa A. Ali (Turkish Journal of Gastroenterology, 2019)
Background/Aims: To find the most accurate, suitable, and applicable scoring system for the prediction of outcome in cirrhotic patients with bleeding varices. Materials and Methods: A prospective study was conducted comprising 120 cirrhotic patients with acute variceal bleeding who were admitted to Tropical Medicine and Gastroenterology Department in Sohag University Hospital, over a 1-year period (1/2015 to 1/2016). The clinical, laboratory, and endoscopic parameters were studied. Child–Turcotte–Pugh (CTP) classification score, Model for end-stage liver disease (MELD) score, acute physiology and chronic health evaluation II (APACHE II) score, sequential organ failure assessment (SOFA) score, and AIMS65 score were calculated for all patients. Univariate and multivariate analyses were performed for all the measured parameters and scores. Results: Of the 120 patients (92 male) admitted during the study period, eight patients (6.67%) died in the hospital. Advanced age, the presence of encephalopathy, rebleeding, and higher serum bilirubin were independent factors associated with higher hospital mortality. The largest area under the receiver operator curve (AUROC) was obtained for the AIMS65 score and SOFA score, followed by the MELD score and APACHEII score, then CTP score, all of which achieved very good performance (AUROC>0.8). AIMS65 score showed the best sensitivity, specificity, and negative and positive predictive values. Although the AIMS65 score was not significantly different from the MELD, SOFA, and APACHEII scores, it was the optimum among them in terms of the prediction of mortality. Conclusion: AIMS65 score is the best simple and applicable scoring system for independently predicting mortality in cirrhotic patients with acute variceal bleeding.